2009
DOI: 10.1021/jo9013657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Carbocyclic Locked Nucleic Acid Analogues by Ring-Closing Diene and Enyne Metathesis and Their Influence on Nucleic Acid Stability and Structure

Abstract: A series of bicylic 2'-deoxynucleosides that are locked in the N-type conformation due to three-carbon linkages between the 2'- and 4'-positions have been prepared by ring-closing diene or enyne metathesis. The alkene or 1,3-diene hereby introduced in the bicyclic system is further derivatized, the latter showing the expected potential for Diels-Alder reactions. Four derivatives that are saturated or unsaturated as well as functionalized at the 2'-4'-linkage are incorporated into oligodeoxynucleotides, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Nielson and coworkers recognized the potential of enyne metathesis in their synthesis of a bicyclic 2 0 -deoxynucleoside, a carbocyclic-locked nucleic acid analog (equation 44). 102 The enyne was subjected to the second-generation Grubbs catalyst using microwave heating for 2 h, giving the bicyclic structure in 82% yield. A tandem metathesis sequence allowed access to an unusual ring-closure mode.…”
Section: ð43þmentioning
confidence: 99%
“…Nielson and coworkers recognized the potential of enyne metathesis in their synthesis of a bicyclic 2 0 -deoxynucleoside, a carbocyclic-locked nucleic acid analog (equation 44). 102 The enyne was subjected to the second-generation Grubbs catalyst using microwave heating for 2 h, giving the bicyclic structure in 82% yield. A tandem metathesis sequence allowed access to an unusual ring-closure mode.…”
Section: ð43þmentioning
confidence: 99%
“…3234 Recently, Nielsen and co-workers reported the synthesis and biophysical properties of a number of carbocyclic ENA analogs using an intramolecular RCM and ene-alkyne metathesis reactions ( 1d–f , Figure 2). 35,36 All the cLNA and cENA analogs reported thus far show moderate to significantly reduced binding affinity for complementary RNA relative to LNA that can be partially restored by introducing hydrophilic groups along the 2’,4’-bridging substituent. Interestingly, both Chattopadhyaya and Nielsen also showed that cLNA analogs appear to recognize complementary DNA less efficiently relative to RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both Chattopadhyaya and Nielsen also showed that cLNA analogs appear to recognize complementary DNA less efficiently relative to RNA. They proposed that replacing the 2’oxygen atom with carbon reduces the hydration of the duplex in the minor groove which in turn affects recognition of DNA more severely as compared to RNA 34,35. Recently, Bramsen and co-workers have reported on the utility of cLNA ASOs for positional modification of sense and antisense strands of siRNAduplexes.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA affinity of cLNA-modified oligonucleotides can be partially restored by introducing polar functionality on the 2′,4′-bridge of these analogues. 9 The polar functionality helps to restore the water of hydration network in the minor groove which is important for maintaining the stability of oligonucleotide duplexes. 10 Interestingly, the cLNA analogue 8 , in which the 2′-oxygen atom was replaced with a exocyclic methylene group, showed LNA-like duplex stabilization properties while the corresponding saturated analogues ( 9 and 10 ) were less stabilizing.…”
mentioning
confidence: 99%